A review of relationship between presenting symptoms and tumour location in colorectal carcinoma in tertiary centre hospital - Zaid Maad Ahmed Samem; Micheal Wong Pak Kai; Mohd Firdaus Mohd Hayati; Nik Amin Sahid Nik Lah; Nornazirah Azizan; Wan Zainira Wan Zain; Andee Dzulkarnaen Zakaria (2018)
Colorectal cancer is ranked as the most common cancer for men and the second most common cancer for women according to the Malaysian National Cancer Registry Report (MNCR) 2007-2011. However, delay in the diagnosis of colorectal cancer is still common partly attributable due to late presentation and incorrect diagnosis by the general practitioners. The aim of this study is to determine the relationship between presenting symptoms of colorectal cancer to the location of the tumour in order to prevent delay in diagnosis of colorectal cancer. Between 1996 until 2009, a total of 212 patient data from Hospital Universiti Sains Malaysia were retrospectively analyzed. The demographic and surgical data were obtained. We studied the relationship of the presenting symptoms of colorectal cancer to the location of the tumour. The age of candidate included in this study range from 16 to 93 years old with mean age was 56 and male predominance. In this study, there is a strong relationship between presenting symptoms and the location of the colorectal cancer but no significant relationship between age and sex to the anatomical location of the tumour. The study showed the presenting symptoms of rectal bleeding, change in bowel habit and tenesmus were significantly associated with rectal tumor, intestinal obstruction with left sided tumors and anemia and abdominal mass with right sided tumors (p-value <0.05). However abdominal pain does not follow this role as it is mostly associated with other presenting symptoms and it has no significant relation to the anatomical location of the tumor.